Cluster Analysis of Properties of Temperament - A I Krupnov (Peoples' Friendship University of Russia (RUDN University), 2014)
The paper presents the cluster analysis of various properties of temperament, based on the systematic structure of its main components. On the basis of the received data the qualitative psychological characteristic of the four types of temperament is given.